Do physical fitness and motor skill performances in underweight children differ from normal weight peers? A meta-analysis - Yabsra Melaku Dubale; Tefera Belachew; Beyene Wondafrash; Eugene Rameckers; Evi Verbecque (BMC Pediatrics)
Abstract Background Undernourished children are at risk of mortality and infection and tend to present with impaired cognitive and physical development with potentially lower physical fitness and motor skill competence. This meta-analysis aimed to compare the physical fitness and motor skill competence of underweight (UW) 3–12-year-old children to that of normal-weight (NW) peers of the same age. Methods PubMed, Web of Science, and Scopus were systematically searched (last update: April 4th, 2024). The methodological quality of the studies was assessed with the Scottish Intercollegiate Guideline Network checklist. Pooled standardized mean differences (SMD; Hedges’ g) were calculated using random-effects meta-analyses. Heterogeneity was considered too high if the I-squared value exceeded 50%. Then, subgroup analysis was considered. The level of evidence was estimated using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) method. Results Seventeen studies were included in the meta-analysis on physical fitness, while six focused on motor skills, with one study contributing to both. Overall, children with UW have slightly lower physical fitness (SMD = -0.10) and motor skill competence (SMD = -0.12) compared to their NW peers, but the evidence to support this is very low. In North America and Europe, there was no significant difference in physical fitness between the groups. Asian and African children with UW have slightly but significantly weaker strength than NW peers (Asia: SMD = -0.21 Africa: SMD = -0.27). Asian UW children present with weaker anaerobic capacity (SMD = -0.25), whereas African UW children have less flexibility (SMD = -0.16) than NW peers. Conclusion UW children are less fit and have weaker motor skills than NW peers. Specifically in developing regions, UW children exhibited slightly but significantly poorer performance in specific fitness domains. Therefore, not all UW children will experience these problems. The heterogeneity across the studies may have masked the true differences. Future research on these children is needed to help us understand their profiles better. PROSPERO registration number CRD42023446239.